2020
DOI: 10.34133/2020/1986576
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Stable and Potentially High-Performance Hybrid Organic-Inorganic Perovskites with “Unstable” Cations

Abstract: A new family of functional hybrid organic-inorganic perovskites (HOIPs) is theoretically designed based on the following chemical insights: when a proton is adhered to molecules like water or ethanol, the newly formed larger-sized cations (e.g., H5O2+, C2H5OH2+, and CH3SH+) entail low electron affinities mimicking su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, we acknowledge that the accuracy of DFT calculations can be enhanced by using dispersion corrections when estimating dispersion effects in perovskite systems. [21][22][23] All calculations have been performed spin-polarized and without symmetry constraints. Electronic wave functions were expanded to an energy cutoff of 650 eV.…”
Section: Methodsmentioning
confidence: 99%
“…However, we acknowledge that the accuracy of DFT calculations can be enhanced by using dispersion corrections when estimating dispersion effects in perovskite systems. [21][22][23] All calculations have been performed spin-polarized and without symmetry constraints. Electronic wave functions were expanded to an energy cutoff of 650 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the record for photovoltaic efficiency, higher than 25%, was achieved in hybrid perovskites. , Although those 2D structures possess chemical stability higher than that of the well-known MAPbI 3 , their band gaps are over 3 eV, which is not within the desirable solar range. A potential ideal candidate is 2D (C 2 H 5 OH 2 ) 2 SnI 4 , which was predicted to possess a band gap of ∼1.7 eV (Figure b) and a switchable in-plane polarization of 1.2 × 10 –10 C/m. Li et al predicted that 2D carbon nitrides may enable “facile functionalization”, forming FE structures (see Figure c) when wetted by a solution of metal halides with mobile cations/anions, with each cavity spontaneously functionalized by a unit of metal halide inside.…”
Section: Semiconductor Propertiesmentioning
confidence: 99%
“…Also, the cationic part of H 5 O 2 + Cl – , the so-called Zundel-type cation H 5 O 2 + , is a very important hydrated proton ubiquitous in solutions and water–solid interfaces, and the incorporation of this cation into the host crystal will enhance host–guest interaction through hydrogen bonding. More importantly, it is reported that once bonded with water molecules, the proton behaves like alkali cations with a much-reduced electron affinity. , This value-added feature along with the expanded ion radius , is of particular importance for the formation of new LDMHs.…”
Section: Introductionmentioning
confidence: 99%